Pengaruh Social Media Marketing dan Customer Online Review terhadap Keputusan Pembelian Somethinc - Nerly Ovirya; Marheni Eka Saputri (SAFE-Network, 2023)
Nowadays, the rise of local beauty brands is proof that the domestic beauty industry is growing and increasingly trusted by consumers. It is known from many local beauty brands that offer quality products at affordable prices. Somethinc is a newcomer local brand that was launched in 2019. Somethinc has managed to attract the hearts of Indonesian consumers with its quality, innovative, and suitable products. Somethinc's success as a newcomer local brand is also an inspiration for other beauty brands to continue to innovate and develop in Indonesia's increasingly competitive beauty industry. This research is quantitative with a survey method conducted to people who know Somethinc products. The sampling technique is non-probability sampling. The sample of this study was 400 respondents. Data analysis was carried out by multiple linear regression analysis. After the research was conducted, it was found that there was an influence between social media marketing partially and significantly on Purchasing Decisions at Somethinc, there was an influence between customer online reviews partially and significantly on Purchasing Decisions at Somethinc, and there was an influence of social media marketing and customer online reviews on Purchasing Decisions at Somethinc.